Sintesis Pemikiran Fonologi Al-Khalīl ibn Aḥmad dan Teori Fonologi Generatif Noam Chomsky dalam Analisis Struktur Bunyi Bahasa Arab - Munawarah; Andi Abdul Hamzah; Baso Pallawagau (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze and synthesize classical and modern phonological thought in the study of Arabic sounds through a comparative study between Al-Khalīl ibn Aḥmad and Noam Chomsky's generative phonological theory. The classical Arabic phonological tradition pioneered by Al-Khalīl through Kitāb al-‘Ayn provides a strong descriptive-empirical basis for the Arabic sound system, especially through the concepts of makhārij al-ḥurūf, ṣifāt al-ḥurūf, and i‘tilāf al-ḥurūf. Meanwhile, the generative phonological theory developed by Chomsky and Morris Halle offers a cognitive-theoretical approach by emphasizing abstract representation, transformation rules, and distinctive features in sound processing. This study uses a qualitative method with a literature study design, through content analysis and a comparative approach to primary and secondary literature. The results of this study indicate that both approaches share common ground in viewing language as an ordered system, but differ in their epistemological orientation: classical phonology starts from articulatory observations, while generative phonology emphasizes the speaker's mental system. The synthesis of the two produces an integrative phonological model capable of explaining Arabic sound phenomena from both physiological and cognitive perspectives. This study is expected to enrich the development of contemporary Arabic phonological theory and open up opportunities for more comprehensive further research.